Bentuk-Bentuk Modernisasi Pertanian di Desa Teamusu Kecamatan Ulaweng Kabupaten Bone Sulawesi Selatan - Bagas, Bagas; Radjab, Mansyur; Sakaria, Sakaria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Modernization of agricultural is a change which occurs in the society from various phases in the agricultural process, starting from using traditional simple tools to using modern tools. This research aimed to analyze what forms of agricultural modernization which exist in Teamusu Village, Ulaweng District, Bone, South Sulawesi. The research method used was descriptive qualitative. The informants of this research were some various elements of the society in Teamusu Village. Data collection techniques in this research including observation, interviews, and documentation. The results showed that the forms of agricultural modernization in the Teamusu Village society included various aspects or phases of the agricultural procession, from land management to the post-production phase, which led to the significant changes. However, not all the lines had changed completely, but only some of it that had been touched by modernization. The existence of this modernization had a positive impact on the society, especially on the energy efficiency and the level of society welfare which was getting better.